Experiences gained through absorption of and immersion in destinations' food event : case evidence from Finnish travellers - Björk, Peter; Kauppinen-Räisänen, Hannele (Elsevier, 2020)
A destination’s foodscape comprises various food events. It invites travellers to gain experiences by staying passive and absorbing information or participating in the events in a multisensory and immersive manner. This study aims to explore the various roles of travellers at their destinations’ food events and the importance of the basic human senses for travellers’ food experiences. The empirical data were collected by means of a self-administered questionnaire distributed to Finnish travellers at the MATKA Nordic Travel Fair in Helsinki. The empirical findings validate previous studies claiming that food and eating experiences at destinations contribute to travel satisfaction. The findings also show that experiences are gained through the absorption of and immersion in destinations’ food events. Both provide experience value to travellers. In addition, the findings have implications for destinations’ marketing organisations in showing that a destination’s foodscape can and should combine different types of food events.
Keywords: Absorption; food events; immersion; sensual stimulation; experiences; fi=Markkinointi|en=Marketing|